Briefe vom Kaiserhof - Schmidt, Ondřej (2022)
Title in English: Letters from the Imperial Court: The Last Luxembourgs in the Diplomatic Correspondence from the Gonzaga Archive in Mantua (1380–1436) The publication brings a critical edition of Latin and Italian correspondence from the court of the Holy Roman Kings or Emperors Wenceslas (1376–1400/1419) and Sigismund (1410/1411–1437), preserved in the archives of the Gonzaga family in Mantua. The edition contains 52 documents, including letters and mandates of the two Luxembourg monarchs and their officials, but most importantly dispatches sent by Gonzaga envoys from the imperial court to Italy. The individual sources shed new light on Wenceslas and Sigismund as rulers and offer a vivid insight into the life of the court, the practice of diplomacy and the everyday life of travel. In addition, they provide an interesting picture of Bohemian and German lands in the Late Middle Ages from the perspective of Italian observers.